Anti-allodynic Effect of Mangiferin in Rats With Chronic Post-ischemia Pain: A Model of Complex Regional Pain Syndrome Type I - Garrido-Suárez, Bárbara B.; Garrido, Gabino; Castro-Labrada, Marian; Pardo-Ruíz, Zenia; Bellma Menéndez, Addis; Spencer, Evelyn; Godoy-Figueiredo, Jozi; Ferreira, Sergio H.; Delgado-Hernández, René (Frontiers in Pharmacology, 2018)
The present study reproduces chronic post-ischemia pain (CPIP), a model of complex regional pain syndrome type I (CRPS-I), in rats to examine the possible transient and long-term anti-allodynic effect of MG; as well as its potential beneficial interactions with some standard analgesic drugs and sympathetic-mediated vasoconstriction and vasodilator agents during the earlier stage of the pathology. A single dose of MG (50 and 100 mg/kg, p.o.) decreased mechanical allodynia 72 h post-ischemia-reperfusion (I/R). MG 100 mg/kg, i.p. (pre- vs. post-drug) increased von Frey thresholds in a yohimbine and naloxone-sensitive manner. Sub-effective doses of morphine, amitriptyline, prazosin, clonidine and a NO donor, SIN-1, in the presence of MG were found to be significantly anti-allodynic. A long-term anti-allodynic effect at 7 and 13 days post-I/R after repeated oral doses of MG (50 and 100 mg/kg) was also observed. Further, MG decreased spinal and muscle interleukin-1β concentration and restored muscle redox status. These results indicate that MG has a transient and long-term anti-allodynic effect in CPIP rats, that appears to be at least partially attributable to the opioid and α2 adrenergic receptors. Additionally, its anti-inflammatory and antioxidant mechanisms could also be implicated in this effect. The association of MG with sub-effective doses of these drugs enhances the anti-allodynic effect, however an isobolographic analysis should be performed to define a functional interaction between them. These findings suggest the possible clinical use of MG in the treatment of CRPS-I in both early sympathetically maintained pain and long-term sympathetically-independent pain.